The rise of the medieval world, 500-1300 : a biographical dictionary - Schulman, Jana K., 1959- (Great cultural eras of the Western world., 2002)
Beginning in 500 with the fusion of classical, Christian, and Germanic cultures and ending in 1300 with a Europe united by a desire for growth, knowledge, and change, this volume provides basic information on the significant cultural figures of the Middle Ages. It includes over 400 people whose contributions in literature, religion, philosophy, education, or politics influenced the development and culture of the Medieval world. While focusing on Western European figures, the book does not neglect those from Byzantium, Baghdad, and the Arab world who also contributed to the politics, religion, and culture of Western Europe.